Anthropological Critique of Islamic Philosophy of Transhumanism: An Analysis of the Concepts of Homo Deus and ʻAbd Allāh - Muhammad Hanif Fuadi; Oby Ara Afima; Mustafa Okleh; Irshad Alrawadieh (Yayasan Albahriah Jamiah Indonesia, 2026)
The development of transhumanism as a contemporary philosophical and technoscientific movement encourages the redefinition of humanity through biological, cognitive, and moral enhancements, culminating in the concept of Homo Deus as a posthuman, autonomous subject. This discourse raises philosophical questions about the nature of humanity, the limits of agency, and the relationship between technology and existential meaning. This study aims to critically analyze the ontological, epistemological, and teleological constructions of Homo Deus and evaluate them through the concept of ‘Abd Allāh in Islamic philosophical anthropology. This research is a literature study with a philosophical-critical and comparative-dialogical approach, employing a conceptual analysis of the main works of transhumanism, especially those of Yuval Noah Harari, as well as the treasures of classical and contemporary Islamic philosophy. The results show that Homo Deus is built on a naturalistic-reductionistic ontology that views consciousness as a computational process and the body as an object of technological optimization. Its epistemology is technocentric by placing data, predictability, and algorithmic efficiency as the main parameters of truth. The teleology of transhumanism equates human perfection with expanded control over the body, emotions, and death. In contrast, the concept of ‘Abd Allāh is rooted in the monotheistic paradigm, which positions humans as relational subjects, ontologically limited, yet valued through moral mandates and ethical responsibilities. This research asserts that Islamic philosophical anthropology offers a conceptual correction to transhumanism by placing human freedom within the horizons of transcendence, ethics, and normative responsibility.